Nanomanufacturing and Metrology - Fang, Fengzhou; Gao, Wei.; He, Jingjing; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Nanomanufacturing and Metrology is a peer-reviewed, international and interdisciplinary research journal and is the first journal over the world that provides a principal forum for nano-manufacturing and nano-metrology. Nanomanufacturing and Metrology publish in the form of original articles, cutting-edge communications, timely review papers, technical reports, and case studies. Special issues devoted to developments in important topics in nano-manufacturing and metrology will be published periodically. Nanomanufacturing and Metrology publishes articles that focus on, but are not limited to, the following areas: Nano-manufacturing and metrology Atomic manufacturing and metrology Micro-manufacturing and metrology Physics, chemistry, and materials in micro-manufacturing, nano-manufacturing, and atomic manufacturing Tools and processes for micro-manufacturing, nano-manufacturing and atomic manufacturing.
Keywords: Microtechnology; Microelectromechanical systems; Nanotechnology; Manufactures; Microsystems and MEMS; Nanotechnology; Machines, Tools, Processes